Analysis of the effect of mind mapping studies on the acquisition of the concept of time among 60-72 month-old children - POLAT, ÖZGÜL (My University, 2022)
This study aims to analyze the effect of mind mapping studies on the acquisition of the concept of time among 60-72 month-old children. The research was conducted with 30 children who attend a preschool in Istanbul. The Mind Mapping: Concept of Time Program was applied to 15 children in the experimental group of the study, for 12 weeks. Pre-test and post-test data for the study were gathered through the Time Concept Achievement Assessment Scale. It was found that the total post-test scores of the children in the experimental group obtained using the scale and their total post-test scores obtained from the Sub-Scales of Before-Now-After, Morning-NoonEvening-Night, Month, Year, and Time Indicator Tools were significantly higher than those of the children in the control group. As a result of the study, it was set forth that mind mapping studies are an effective strategy for children’s acquisition of the concept of time.
Keywords: Acquisition of the concept of time; Mind mapping; Mind mapping intervention; Early childhood; Pre-schoolers